An examination of the e-mail and electronic relationship marketing practices of the USA's top 500 online retailers. (2016) - Heiens, Richard A.; Narayanaswamy, Ravi
The present study analyses the relationship between the relative size of an internet retailer in terms of annual sales and their use of e-mail marketing and electronically mediated relationship marketing strategies. The results reveal that the majority of the USA's top 500 online retailers do in fact rely on e-mail marketing programs and that higher-ranked companies actually send more e-mails per customer per year than their lower-ranked counterparts. Also, higher-ranked online retailers are not as likely to permanently include an 'opt-in' choice on their websites, although they are more likely to send a series of welcome e-mails. Moreover, there is partial support that higher-ranked online retailers are more likely to utilise incentive offers. Finally, higher-ranked online retailers are more likely to include links to social networks on their websites.